Repair index method to evaluate the condition of reinforced concrete structures exposed to reinforcement corrosion - 454678 Muhammad Ismail; Universiti Teknologi Malaysia. Fakulti Kejuruteraan Awam (Skudai, Johor : Penerbit UTM, 2008)
Includes bibliographical references